Sustainability and Poverty Alleviation : Confronting Environmental Threats in Sindh, Pakistan - Sánchez-Triana, Ernesto; Enriquez, Santiago; Larsen, Bjorn; Webster, Peter; Afzal, Javaid (Washington, DC: World Bank, 2015)
The underlying goal of this book is to facilitate and stimulate sharing of information on these phenomena and to provide an interdisciplinary framework for bringing about improved environmental conditions in Sindh. The book offers methods to identify environmental and climate change priority problems; analyzes interventions to address such problems; establishes a social learning mechanism to continuously improve Sindh’s responses and build resilience to climate variability and change; and provides opportunities for stakeholders to be involved in decisively tackling climate change and deteriorating environmental conditions.